Dinamika Kedudukan, Peran Dan Status Perempuan Suku Asmat Pendekatan Arena Kultural Pierre Bourdieu - Godefridus Samderubun; Anis Izdiha (SOCIETAS, 2023)
Asmat Tribe women are faced with a subordinate position because of the social transformation that has occurred in Asmat Tribe due to the intervention of 'outsiders'. The existence of the Asmat tribe is an attraction for missionaries, countries and also other practitioners who attend with their own goals. This study describes the phase of social transformation that occurred in Asmat Tribe which has changed the social construction of the status, role and position of women in it. The research method used is a qualitative descriptive analysis method that focuses on Pierre Bourdieu's theory of the cultural arena as a rationale. The results of the study show that the status, role and position of women experience a dynamic change from a dichotomous pattern to a subordinate one due to the interference of "outsiders". In the phase before the missionaries arrived, social roles within the Asmat tribe were not only determined by gender and kinship but also skills and knowledge, whereas during the missionary phase, women began to accept subordinate behavior because the teachings in the Bible seemed to legitimize the existence of male roles. -males are taller than females. Likewise, when the state came to the Asmat, women were increasingly entangled in domestic terms as the main space for women. Asmat Tribe women are faced with a subordinate position because of the social transformation that has occurred in Asmat Tribe due to the intervention of 'outsiders'. The existence of the Asmat tribe is an attraction for missionaries, countries and also other practitioners who attend with their own goals. This study describes the phase of social transformation that occurred in Asmat Tribe which has changed the social construction of the status, role and position of women in it. The research method used is a qualitative descriptive analysis method that focuses on Pierre Bourdieu's theory of the cultural arena as a rationale. The results of the study show that the status, role and position of women experience a dynamic change from a dichotomous pattern to a subordinate one due to the interference of "outsiders". In the phase before the missionaries arrived, social roles within the Asmat tribe were not only determined by gender and kinship but also skills and knowledge, whereas during the missionary phase, women began to accept subordinate behavior because the teachings in the Bible seemed to legitimize the existence of male roles. -males are taller than females. Likewise, when the state came to the Asmat, women were increasingly entangled in domestic terms as the main space for women.